Pengembangan Media Ular Tangga Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS di SD - Bella Tri Arumsari; Dian Nur Antika Eky Hastuti; Maya Kartika Sari (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This research aims to develop snakes and ladders game media to improve student learning outcomes in social studies subjects in elementary schools. This research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This researcher produced a snakes and ladders game media product to overcome students' boredom and saturation in learning. In this development the media was validated by 2 validators and there was a teacher and student response questionnaire to determine the suitability of the media. Meanwhile, to determine the increase in student learning outcomes, pretests and posttests were given to students. The calculation results obtained the completeness of the game media by achieving a score of 93.36% for media experts, 95.38% for material experts, and teacher responses were obtained 84.61%, to find out the percentage of student responses to the questionnaire totaling 26 students, an average calculation was carried out and a score of 93.69% was obtained. Meanwhile, for student learning outcomes, the average was 0.57 which was calculated using the N Gain score formula. You can It was concluded that the snake and ladder game media was included in the valid category or suitable for use for learning in class IV elementary schools.